پیر نصیر الدین نصیر ؒکی نعتیہ شاعری میں عشق رسول ﷺ کے نقوش - Dr. Amir Hayat (Al Manhal Research Journal, 2025)
There have been many fortunate individuals in this world whose lives were an example of love for the Prophet (peace and blessings of Allah be upon him). Among these fortunate individuals was a lover of the Prophet born in Islamabad, capital of Pakistan in the 20th century. The name of this fortunate lover of the Prophet was Pir Syed Nasiruddin Nasir. He was born on 14 November 1949, corresponding to 22 Muharram 1369 AH, in Golra Sharif, Islamabad, Pakistan. He belonged to a Spiritual and scholarly family. Pir Syed Naseeruddin Naseer was a renowned religious scholar and a prodigious poet. He was simultaneously a poet, writer, researcher, orator, scholar and a Sufi. He had equal command over Urdu, Persian, Arabic, Punjabi, Hindi and Saraiki languages. He inscribed poems in all these languages. He has been given the title of “poet of the seven languages”. The entire life of Pir Syed Nasiruddin Nasir was spent in spreading the message of love for the Prophet (peace and blessings of Allah be upon him). When he used to spoke, he would pour out the cup of love for the Prophet in the form of words. When he picked up the pen, he seemed to be promoting the love for the Prophet in the form of writing. It was as if every moment of his life was spent in drinking and pouring out the cup of love for the Prophet. His poetry reveals his true love for the Prophet. Especially his collection of Naat poetry, Deen Huma Awast, is a incredible sign of his love for the Prophet. "Deen Huma Awast", came to the fore for the second time in 2002. This Naat collection includes Naats in Persian, Urdu, Arabic and Punjabi languages. Since the axis and center of Naat is the personality of the Holy Prophet (peace and blessings of Allah be upon him). In this collection the love for the personality, biography and the affairs of the Holy Prophet (peace and blessings of Allah be upon him) is seen at its peak. Pir Syed Nasiruddin Nasir has described many aspects of love for the Prophet (peace be upon him) in his Naats. The article under consideration presents an analytical study of the Naatiya poems related to the love of the Holy Prophet (peace and blessings of Allah be upon him) and its requirements.